Radiographic Characteristics of Soft Tissue Calcification on Digital Panoramic Images - Samira Saati; Maryam Foroozandeh; Behnaz Alafchi (Association of Support to Oral Health Research (APESB), 2022)
Objective: To assess the prevalence of soft tissue calcifications and their panoramic radiographic characteristics. Material and Methods: This descriptive retrospective study evaluated 2027 panoramic radiographs. The type and location of calcifications and the age and gender of patients were evaluated by two radiologists. Data were analyzed via SPSS and the Chi-square, Fisher's exact and Kappa tests were used to compare the categorical demographic variables among the groups. The confidence interval was set to 95% and p<0.05 was considered statistically significant. Results: The prevalence of calcified stylohyoid ligament was 11.24%. This value was 3.99% for tonsillolith, 1.33% for calcified carotid plaque, 0.69% for antrolith, 0.39% for calcified lymph node, 0.29% for phleboliths, and 0.19% for sialoliths. The prevalence of these conditions had no significant association with gender or age (p=0.102). The prevalence of bilateral calcified stylohyoid ligament, tonsillolith, and a calcified carotid plaque was significantly higher (p<0.001). The most prevalent type of calcified stylohyoid ligament, according to O'Carroll's classification, belonged to types 1, 4, 3 and 2 (p<0.001). The most commonly observed radiographic pattern was multiple, well-defined tonsilloliths (75.3%, p<0.001). Conclusion: The prevalence of soft tissue calcifications on panoramic radiographs was relatively low in this Iranian population. The most calcifications were respectively calcified stylohyoid ligament, tonsillolith, calcified carotid plaque, antrolith, calcified lymph node, phleboliths and sialoliths. Calcified stylohyoid ligament, tonsillolith and calcified carotid plaque were more bilaterally. Thereby panoramic imaging can help in primary assessment, epidemiologic and screening evaluation of these calcifications.